Pulse train‐controlled CCM boost converter with suppression of low‐frequency oscillation. Issue 8 (1st June 2017) - Xu, Ruidong; Zhang, Yong; Lu, Shengli; Chen, Guipeng; Yu, Dongsheng; Wang, Long
Abstract : In the conventional boost converter with pulse train (PT) control, the output voltage will produce undesirable low‐frequency oscillation in continuous conduction mode. To alleviate the problem, this study proposes a novel boost converter in which much more energy can be delivered when the output voltage is less than the reference and vice versa, the energy delivery is suppressed. The response speed of the proposed converter is greatly improved and low‐frequency oscillation is reduced. Firstly, the low‐frequency oscillation of the PT‐controlled conventional boost converter is analysed. Furthermore, the operating principles of the proposed boost converter are studied. Then the processes of start‐up and load switching are simulated. The waveforms of the steady‐state operation and the transient response of the load change are illustrated through experimental results, which indicate that the novel boost converter outperforms the traditional one in fast response, short start‐up time, small overshoot, wide load range and effective suppression of low‐frequency oscillation.